Combined Analysis of the Transcriptome and Metabolome Revealed the Mechanism of Petal Coloration in Bauhinia variegata - Zhang, Geng; Yang, Xiaohui; Xu, Fang; Wei, Dan (Frontiers in Plant Science, 2022)
Bauhinia variegata petals are colorful, rich in anthocyanins, and have important ornamental, edible, and medicinal value. However, the regulatory mechanism of anthocyanin accumulation in B. variegata has remained unclear. In this study, a combined analysis of the metabolome and transcriptome was performed in two B. variegata cultivars, one white and the other red. Overall, a total of 46 different anthocyanins were identified, of which 27 showed marked differences in accumulation between the two cultivars, contributing to the different petal colors of B. variegata. Moreover, malvidin 3-O-galactoside, peonidin 3-O-galactoside, cyanidin 3-O-glucoside, cyanidin 3-O-galactoside, and malvidin 3-O-glucoside were much more abundant in the second stage of flowering. In the third stage, except for the anthocyanins mentioned above, delphinidin 3-O-galactoside and petunidin 3-O-galactoside were the most abundant anthocyanins in the red flowers, indicating that malvidin, peonidin, cyanidin, delphinidin, and petunidin are all responsible for the red color of petals in B. variegata. RNA sequencing results were used to identify 2,431 differentially expressed genes (DEGs), of which 26 were involved in the anthocyanin synthesis pathway. The correlations between the anthocyanin-biosynthesis-related DEGs and anthocyanin contents were explored. The DEGs involved in anthocyanin accumulation in the B. variegata petals were identified, of which 18 were genes encoding key catalytic enzymes such as anthocyanidin reductase (ANR) and flavonoid-3'5'-hydroxylase (F3'5'H), and 81 encoded transcription factors belonging to 35 families (including MYB, NAC, SPL, ERF, WRKY, ARF, MADS, and bHLH). Our results provide deeper knowledge of anthocyanins and their important catalytic enzymes and transcription factors in B. variegata petal color expression.